Senescent-like Blood Lymphocytes and Disease Progression in Amyotrophic Lateral Sclerosis. Issue 1 (2nd January 2023) - Yildiz, Ozlem; Schroth, Johannes; Tree, Timothy; Turner, Martin R.; Shaw, Pamela J.; Henson, Sian M.; Malaspina, Andrea
Abstract : Background and Objectives: Aging is known to exacerbate neuroinflammation, and in the neurodegenerative disorder amyotrophic lateral sclerosis (ALS), an older age is associated with a worse prognosis. We have previously shown the activation of cell senescence pathways in the proteome of peripheral blood mononuclear cells and the increase of proinflammatory cytokines in blood from individuals living with ALS. In this single-center, retrospective study, we investigated the expression of senescent-like blood mononuclear cells in ALS. Methods: We first applied multidimensional cytometry by time-of-flight (CyTOF) to study the senescent immunophenotype of blood mononuclear cells from 21 patients with ALS and 10 healthy controls (HCs). We then used targeted flow cytometry (FC) to investigate frequencies of senescent blood lymphocytes in 40 patients with ALS and 20 HCs. Longitudinal analysis included 2 additional time points in 17 patients with ALS. Frequencies of senescent-like lymphocytes were analyzed in relation to survival. Results: Unsupervised clustering of CyTOF data showed higher frequencies of senescent CD4 + CD27 − CD57 + T cells in patients with ALS compared with those in HCs ( p = 0.0017, false discovery (FDR)-adjusted p = 0.029). Moderate to strong negative correlations were identified between CD4 T central memory–cell frequencies and survival (R = −061, p = 0.01; FDR-adjusted p < 0.1) and between CD95 CD8 cells and ALS functional rating scale revised at baseline (R = −0.72, p = 0.001; FDR-adjusted p < 0.1).Targeted FC analysis showed higher memory T regulatory cells ( p = 0.0052) and memory CD8 + T cell (M-Tc; p = 0.0006) in bulbar ALS (A-B) compared with those in limb ALS (A-L), while late memory B cells (LM-B) were also elevated in A-B and fast-progressing ALS ( p = 0.0059). Higher M-Tc levels separated A-B from A-L (AUC: 0.887; p < 0.0001). A linear regression model with prespecified clinical independent variables and neurofilament light chain plasma concentration showed that higher frequencies of LM-B predicted a shorter survival (hazard ratio: 1.094, CI: 1.026–1.167; p = 0.006). Discussion: Our data suggest that a systemic elevation of senescent and late memory T and B lymphocytes is a feature of faster progressing ALS and of ALS individuals with bulbar involvement. Lymphocyte senescence and their memory state may be central to the immune dysregulation known to drive disease progression in ALS and a target for biomarkers and therapeutics discovery.